An inclusive arts-mediated program for children with and without disabilities: Establishing community and an environment for child development through the arts. Issue 2 (2nd April 2016) - King, Gillian; Kingsnorth, Shauna; Sheffe, Sarah; Vine, Robert; Crossman, Shannon; Pinto, Madhu; Curran, C. J.; Savage, Diane
ABSTRACT: This multi-method qualitative study examined the culture, intentional design, and features of a 30-year inclusive arts-mediated summer program called Spiral Garden. The study involved historical document analysis, and interviews with key informants and staff members. Study themes indicated that the Garden was intentionally designed to provide multiple opportunities and points of entry, and to focus on child-directed experiences of freedom/possibility, engagement/connection, and belonging/community. The Garden was viewed as having a principle-based, self-generating culture, where art is the means by which children engage in the community and with one another. The findings are relevant to service providers who deliver inclusive arts-based programs.